Connecting life science entrepreneurs with resources and expertise: the role of iungens brokerage in life science innovation. Issue 6 (2nd July 2016) - Styhre, Alexander; Remneland-Wikhamn, Björn
ABSTRACT: Life science innovation demands detailed expertise at each stage of the development of a commercial product. Besides a perceived shortage of venture capital, venturing life science companies face the challenge of limited access to qualified expertise in regulatory affairs and commercialisation. Examining a bio hub initiative at a major pharmaceutical company, a form of in-house incubator wherein life science companies can both take advantage of laboratory facilities and the stock of expertise of the hosting company, it is argued that such initiatives support the life science innovation field. Taking on an iungens brokerage role, the hosting company effectively connects previously separated actors, thus lowering the transaction costs incurred when accessing qualified scientific, regulatory, and commercial know-how, which are all of great value to life science companies during the venturing phase. The iungens brokerage role thus represents a highly valuable position in the field of life science innovation.